School failure from a psychological point of view - Galindo, Edgar E. (2017)
School failure is an educational problem with multiple causes at different levels. In spite of a set of measures applied by educational agencies during many years, it remains a major problem in Portugal and in other countries, due to a variety of factors. The problem has social and political dimensions and consequently several solutions have been proposed. Nevertheless, solutions must take into account the individual level. This paper analyzes the contribution of Psychology to understand and propose solutions for individual children. A project is presented in which Applied Behavior Analysis techniques are applied to train 6-12 years old children with academic difficulties of very different origins. Training programs for Basic Behavior (precurrents), Social Behavior and Academic Behavior are explained. Results are evaluated in terms of % of attained objectives, time, and (subjective) teachers` satisfaction.